Obtaining mullite from kaolin waste through thermal treatment in conventional oven (Research, Society and Development, 2021)
This work aimed to evaluate the capacity of mullite formation through heat treatment applied to kaolin residue, in which the influence of temperature on the formation of this phase was investigated. Kaolin and commercial kaolin residue samples were calcined at 1100 and 1200°C with heating rates of 2 and 30°C/min, for comparison purposes in obtaining the mullite phase, in conventional oven. Subsequently, the starting samples and the phases obtained were characterized by DRX, FTIR, SEM, EDX, TG/DTA and quantified by the Rietveld method. Results indicated that the raw materials are kaolin with similar structures, containing kaolinite as predominant clay mineral, followed by quartz. Thermal events obtained by TG/DTA evidenced mullite nucleation at approximately 903°C. The thermal treatment applied favored formation of crystalline phases: mullite (32 - 57%), followed by quartz (28 - 63%), an amorphous component rich in silica (11 - 18% of vitreous phase), and, as a minor phase, cristobalite (0.27 - 17%). The morphologies of samples are micro needles, with heterogeneous sizes and distribution. Kaolin tailings, compared to commercial kaolin, showed promising potential as a raw material for obtaining the mullite phase. Such a context entails economic and environmental gains for ceramic industry, since it can replace commercial kaolin in the composition of mass for white ceramics, as well as reducing sintering temperature due to the presence of fluxes such as quartz and feldspar.